First report on the molecular detection of Entamoeba bovis from the endangered wild water buffalo (Bubalus arnee) in Nepal. Issue 2 (17th December 2021) - Aryal, Menuka; Adhikari, Roshan Babu; Kandel, Prakriti; Ghimire, Tirth Raj; Khadka, Deegendra; Maharjan, Jyoti; Gaire, Kamal Prasad; Shrestha, Saurav; Manandhar, Krishna Das; Kandel, Ram Chandra; Poudel, Ram Chandra; Pandey, Kishor
Abstract: Background: The Asiatic wild water buffalo ( Bubalus arnee) is an endangered species that is conserved in the Koshi Tappu Wildlife Reserve (KTWR), Nepal, and was recently translocated to the Chitwan National Park (CNP). Gastrointestinal (GI) parasites are the cause of significant negative health and production impacts on animals worldwide. Methods: A coprological survey of GI parasites of wild water buffalo was carried out in the CNP in 2020. Fresh dung samples (n = 25) were collected from wild water buffaloes and analysed using sedimentation and flotation techniques for morphological identification of parasite cysts, oocysts and eggs. Results: Nine different GI parasites were recorded of which Entamoeba spp. (20 samples, 80%) were the most common. The presence of Entamoeba spp. was further validated using polymerase chain reaction (PCR) analysis and DNA sequencing. The PCR results were positive for all of the microscopically positive samples, and the species was identified as Entamoeba bovis . Three samples were sequenced and formed a cluster of E. bovis, which was separated from other Entamoeba spp. in phylogenetic analysis. Conclusion: This is the first report for molecular detection of E. bovis from wild water buffaloes in Nepal. Future work should focus on the prevalence of such infections in water buffaloes in forest environments. Abstract : 1. The Asiatic wild water buffalo is an endangered species that are present only two areas in Nepal. 2. Microscopic examination revealed 96% prevalence rate with four protozoan and five helminths' parasites detected in wild water buffalo. 3. PCR and sequencing revealed the presence of highly prevalent species as Entamoeba bovis. 4. This is the first molecular report of E. bovis in Nepalese wild water buffaloes.